Social stability risk assessment and economic competitiveness in China - Ruilian Zhang; Sandy Worden; Junzhuo Xu; John R. Owen; Guoqing Shi (Humanities & Social Sciences Communications, 2022)
Abstract Social stability risk assessment (SSRA) has become the mainstream policy instrument for assessing potential risks of large-scale development projects across all sectors in China. In this paper, fuzzy qualitative comparative analysis (fsQCA) is used to quantify the impact of SSRA policy on economic competitiveness across China’s 31 provinces using a SSRA policy dataset (2003–2020) and a provincial economic competitiveness dataset (2019–2020). QCA combines Boolean algebra and set theory to identify configurations of conditions that are necessary or sufficient for a given outcome. Rather than following the mainstream statistical method of developing a single causal model that best fits the data, QCA explores multiple concurrent causality. A typology of SSRA policies was developed to guide our analysis. The research concluded that to support high economic competitiveness within provinces, SSRA policies must be structured around solving social stability problems and addressing a specific industry issue (e.g., pollution) in a particular industry (e.g., resources). Policies that only include one of these factors or that focus on the performance of government officials were found to contribute to low economic competitiveness. Reorienting the focus of SSRA policies could support more rigorous risk assessments and enhance economic competitiveness, particularly in provinces that host large-scale development projects. These findings have implications for China’s policymakers given their dual objectives of driving economic reform while maintaining a harmonious society.